Cobb Syndrome Associated with Spinal Cavernoma – Case Report - Filho, Paulo Moacir Mesquita; Lucena, Luan; Devens, Leticia Bassani; Dias, Luana Rossato; Gregol, Bruno Missio; Azambuja Jr, Nério Dutra (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Cobb syndrome, or cutaneomeningospinal angiomatosis, is a rare condition that affects young adults, and its etiology has not been completely elucidated. It is characterized by a cutaneous sign, or stigma, associated with spinal or intracranial malformations. The symptoms are quite diverse, but, in most cases, the disease presents motor deficit and pain. The present study reports the case of a 48-year-old female patient, who initially sought dermatological medical care for a single skin lesion in the posterior cervical region. During the excision, it was noticed that the lesion had contiguous behavior to the deep anatomical planes, thus requiring the evaluation of the neurosurgical team. The purpose of this report is to describe this rare disease, covering more details about diagnosis and therapy.
Keywords: arteriovenous malformation; nevus; angiomatosis; Cobb syndrome